Production management and improvement initiatives: case studies of two Malaysian manufacturing companies - Ab Latif, Mohd Noor Hisyam (2013)
Currently, there are numerous Production Management and Improvement (PMI) initiatives that can be used by the manufacturing companies such as Lean Manufacturing, Material Requirement Planning, Manufacturing Resource Planning, Six Sigma, Agile Manufacturing and Flexible Manufacturing System. Unfortunately, there are very limited study on the selection and implementation of multiple PMI initiatives especially in Malaysian manufacturing companies. The objectives of this study are to identify the main PMI initiatives currently being implemented by the case companies, investigate the strengths and limitations of the main PMI initiatives, investigate the processes involved in selecting and implementing multiple PMI initiatives, and finally to propose a framework for the selection and implementation of PMI initiatives. The method of data collection in this study involved eight semi-structured interviews, document reviews and observations. Two automotive companies were selected as case companies: (1) Permintex Furukawa Autoparts Sdn. Bhd. and (2) Yokohama Industries Bhd. From the data collected, it was found that the case companies implemented Lean Manufacturing, Material Requirement Planning, Manufacturing Resource Planning, and Six Sigma as their main PMI initiatives. Finally a framework for selection and implementation of PMI initiatives has been developed using the acronym ‘AIR’ which indicates (1) Analyse, (2) Implement, (3) Reflection; with intention to assist organisations in selecting and implementing appropriate PMI initiatives. This study enriches the pool of reference materials and findings related to the selection and implementation of PMI initiatives in the Malaysian manufacturing companies.